The Influence of Railway Infrastructure Development on Regional Economic Growth: Literature Review - Nur Achmad; Agung Riyardi; Mohd Fahmy Abdullah; Mohd Syafiq Syazwan Mustafa; Amirul Ikmal Ramli (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study provides a synthesized critical analysis of theoretical and practical advancements, focusing on their integration.Methodology: A PRISMA systematic literature review of 72 peer-reviewed publications from diverse global contexts was conducted.Results: Findings reveal five key insights: the necessity of a multidisciplinary approach; the critical need to expand research into local contexts and test the relationship between green technology and safety in developing countries; the benefits of integrating advanced technologies for operational efficiency; the role of public policy in inclusivity; and the significance of digital transformation. The study's originality is its holistic, global synthesis. Future research must develop inclusive infrastructure and integrate digital and green technologies through strengthened international collaboration, particularly in underrepresented regions, to support economic growth and global sustainability goals.Applications/Originality/Value: Applications: Policy recommendations for infrastructure in developing countries and the integration of smart technologies (AI, big data, GIS). Originality: A novel classification framework that integrates technology, policy, and digital transformation. Value: Provides a foundation for the development of efficient, safe, and sustainable transportation systems, while addressing global challenges such as climate change and urbanization.